Leaders of IIUM as the 'ibad (slaves, servants) of Allah (S.W.T.) and khulafa' (successors, inheritors, vicegerents) of his earth - Hassan, Mohd. Kamal (2014)
INTRODUCTION: The subject of leadership is undoubtedly one of the most important issues of our times, not least because recent history has shown what excellent and ethical leadership can do to catapult a country or an organization to greater heights, and what mediocre and unethical leadership has done and is doing to destroy nations, states, communities, organisations or movements. Let us recall what Lee Iacocca, the former CEO of Chrysler wrote in his best-selling book in 2007,Where Have All the Leaders Gone?